Access and Use of Digital Technologies in Early Childhood: A Review of Mixed Messages in Popular Media - Teichert, Laura; Anderson, Jim; Anderson, Ann; Hare, Jan; McTavish, Marianne (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
This paper reports on an analysis of 60 print and online articles collected in a metropolitan area in Canada that describe children’s digital engagement through a focus on ‘early literacy’ or ‘digital literacy’. Findings reveal mixed messages about children’s use of digital technology that create competing frames for adults supporting (or not) young children’s digital literacy practices. Digital technology was often characterized as something to limit/control, except in school, where digital literacy was characterized as holding a proper place when controlled by educators. Consistent across media messaging was the promotion of traditional, print-based texts as an essential early literacy practice.